2018
DOI: 10.1136/lupus-2018-000274
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus in non-Asian patients with SLE: a real-life experience from three European centres

Abstract: ObjectivesTo analyse the real-life practice on the use of Tacrolimus (TAC) in patients with systemic lupus erythematosus (SLE) from three European SLE referral centres.MethodsAdult patients with SLE regularly followed at three European referral centres were included. Demographics, cumulative organ involvement, treatment history, Systemic Lupus Disease Activity Index (SLEDAI), laboratory features and physician’s judgement were collected at baseline and at 3–6–12 months after starting TAC.Results29 patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…156 Tacrolimus, a calcineurin inhibitor used as a single agent or in combination with MMF in SLE, has been associated with a relatively low incidence of severe infections in various reports, although data are scarce. 156,176,177 A comparison between SLE patients on sGC and tacrolimus vD 1 4 5 X Xs those on sGC and CYC showed a similar incidence rate of herpes zoster and varicella between the D 1 4 6 X X2 groups. 178 Belimumab, a B lymphocyte stimulator D 1 4 7 X Xinhibitor, is currently the only biologic approved for use in SLE.…”
Section: Commonly Used Drugs In Sle and Predisposition To Viral Infecmentioning
confidence: 92%
“…156 Tacrolimus, a calcineurin inhibitor used as a single agent or in combination with MMF in SLE, has been associated with a relatively low incidence of severe infections in various reports, although data are scarce. 156,176,177 A comparison between SLE patients on sGC and tacrolimus vD 1 4 5 X Xs those on sGC and CYC showed a similar incidence rate of herpes zoster and varicella between the D 1 4 6 X X2 groups. 178 Belimumab, a B lymphocyte stimulator D 1 4 7 X Xinhibitor, is currently the only biologic approved for use in SLE.…”
Section: Commonly Used Drugs In Sle and Predisposition To Viral Infecmentioning
confidence: 92%
“…Tacrolimus, also known as FK506, is a potent immunosuppressor, which, as a first-line drug in liver, kidney and heart transplantation, has come into the market in Japan and the United States in recent years (15). At the same time, it also plays a positive role in the treatment of such autoimmune diseases as atopic dermatitis, systemic lupus erythematosus and autoimmune eye diseases (16)(17)(18). A large number of clinical studies have proved that tacrolimus can significantly reduce the incidence of early initial poor function (IPF), primary nonfunction (PNF) and delayed nonfunction (DNF) caused by ischemia-reperfusion injury after transplantation (19)(20)(21), and ischemia-reperfusion injury is essentially a non-specific inflammatory response, indicating that tacrolimus has an anti-inflammatory property.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, recent research has demonstrated that the combination of MMF and tacrolimus (TAC) at the half dose is more therapeutic than monotherapy in inhibiting MC proliferation in vitro and in vivo ( 130 ). TAC is a valid treatment option for SLE patients with renal involvement ( 131 ). TAC targets the Smad2 signaling pathway, and MMF targets the p38 signaling pathway, both of which could inhibit MC proliferation ( 130 ).…”
Section: The Contribution Of Mc-related Therapeutics To Clinical Trea...mentioning
confidence: 99%